Hierarchical Porous NC@CuCo Nitride Nanosheet Networks: Highly Efficient Bifunctional Electrocatalyst for Overall Water Splitting and Selective Electrooxidation of Benzyl Alcohol. (20th October 2017) - Zheng, Jian; Chen, Xianlang; Zhong, Xing; Li, Suiqin; Liu, Tianzhu; Zhuang, Guilin; Li, Xiaonian; Deng, Shengwei; Mei, Donghai; Wang, Jian‐Guo
Abstract: Highly active and stable bifunctional electrocatalysts for overall water splitting are important for clean and renewable energy technologies. The development of energy‐saving electrocatalysts for hydrogen evolution reaction (HER) by replacing the sluggish oxygen evolution reaction (OER) with a thermodynamically favorable electrochemical oxidation (ECO) reaction has attracted increasing attention. In this study, a self‐supported, hierarchical, porous, nitrogen‐doped carbon (NC)@CuCo2 N x /carbon fiber (CF) is fabricated and used as an efficient bifunctional electrocatalyst for both HER and OER in alkaline solutions with excellent activity and stability. Moreover, a two‐electrode electrolyzer is assembled using the NC@CuCo2 N x /CF as an electrocatalyst at both cathode and anode electrodes for H2 production and selective ECO of benzyl alcohol with high conversion and selectivity. The excellent electrocatalytic activity is proposed to be mainly due to the hierarchical architecture beneficial for exposing more catalytic active sites, enhancing mass transport. Density functional theoretical calculations reveal that the adsorption energies of key species can be modulated due to the synergistic effect between CoN and CuN. This work provides a reference for the development of high‐performance bifunctional electrocatalysts for simultaneous production of H2 and high‐value‐added fine chemicals. Abstract : Hierarchical porous nitrogen‐doped carbon@CuCo2 N x /carbon fiber serving as an efficient bifunctional electrocatalyst for overall water splitting and selective electrooxidation of benzyl alcohol with excellent activity and stability is reported. The outstanding electrocatalytic performance is mainly due to the hierarchical architecture and the synergistic effects between the Co5.47 N, Cu3 N nanoparticles.